2013
DOI: 10.1007/s12355-013-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions from Green-Harvested Sugarcane With and Without Post-harvest Burning in Tucumán, Argentina

Abstract: Concentrations of greenhouse gases (GHG) in the atmosphere are increasing due to anthropogenic actions, and agriculture is one of the most important contributors. This study quantified GHG emissions from greencane harvested sugarcane with and without post-harvest burning in Tucuma ´n (Argentina). A field trial was conducted in Tucuma ´n during the 2011/2012 season using a randomised complete-block design with four replications. Treatments were: (a) harvest without sugarcane burning (neither before nor after), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Environmental conditions and temporal variations can be linked with larger CO 2 emissions by promoting root respiration and organic matter decomposition and stimulating microbial activity. Many studies agree that CO 2 emission rates depend on climate and seasonal variations (Acreche et al, 2014;Chalco Vera & Acreche, 2018;Dhadli et al, 2016;Figueiredo et al, 2015;La Scala et al, 2005;Paustian et al, 2000). The lack of significant differences between the treatments suggests that soil fertilization did not appear to be the main factor controlling CO 2 emissions.…”
Section: Effect Of Environmental Conditions and Nitrogen Fertilizatio...mentioning
confidence: 91%
“…Environmental conditions and temporal variations can be linked with larger CO 2 emissions by promoting root respiration and organic matter decomposition and stimulating microbial activity. Many studies agree that CO 2 emission rates depend on climate and seasonal variations (Acreche et al, 2014;Chalco Vera & Acreche, 2018;Dhadli et al, 2016;Figueiredo et al, 2015;La Scala et al, 2005;Paustian et al, 2000). The lack of significant differences between the treatments suggests that soil fertilization did not appear to be the main factor controlling CO 2 emissions.…”
Section: Effect Of Environmental Conditions and Nitrogen Fertilizatio...mentioning
confidence: 91%
“…ha −1 y −1 [99,100]. However, Acreche et al [118] reported 43% more CO 2 emissions from tillering in the green harvest system and 247% more N 2 O emissions from post-fertilization than in burnt sugarcane, and the authors reported meaningful CH 4 emissions rates compared with those of CO 2 and N 2 O.…”
Section: Green Harvest Managementmentioning
confidence: 97%
“…An increase in air and soil temperatures accelerates organic matter decomposition and the activity of microorganisms and roots (Six et al 2006;Silva-Olaya et al 2013). In its turn, this acceleration influences FCO 2 , which responds linearly to increases in soil temperature (Acreche et al 2013). Thus, assessing this attribute when characterizing the temporal variability of soil CO 2 flux to the atmosphere is very important.…”
Section: Effect Of Cultivars On the Temporal Variability Of Fco 2 Tmentioning
confidence: 99%